2002
DOI: 10.1177/026988110201600116
|View full text |Cite
|
Sign up to set email alerts
|

Does 5-HT restrain panic? A tryptophan depletion study in panic disorder patients recovered on paroxetine

Abstract: The neurobiological basis of panic disorder has not been clearly established, although a role for serotonin (5-HT) has been postulated. It is clear that drugs which increase 5-HT neurotransmission are effective in treating the condition but how they do so remains a point of debate. The aim of this study was to determine if lowering brain serotonin activity using the technique of tryptophan depletion provoked a short-term relapse of panic symptoms in patients with panic disorder who had responded to drug treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 34 publications
(57 reference statements)
2
73
2
3
Order By: Relevance
“…Studies so far have shown that treatment with SSRIs significantly decreased the sensitivity of patients with PD to the panicogenic effects of CCK-4, flumazenil, and CO 2 (Bell et al, 2002;Bertani et al, 1997;Perna et al, 1997;Shlik et al, 1997;van Megen et al, 1997). These results support the view that 5-HT-ergic enhancement by SSRIs leads to antipanic effects.…”
Section: Effects Of Treatment On Panic Challengementioning
confidence: 56%
See 1 more Smart Citation
“…Studies so far have shown that treatment with SSRIs significantly decreased the sensitivity of patients with PD to the panicogenic effects of CCK-4, flumazenil, and CO 2 (Bell et al, 2002;Bertani et al, 1997;Perna et al, 1997;Shlik et al, 1997;van Megen et al, 1997). These results support the view that 5-HT-ergic enhancement by SSRIs leads to antipanic effects.…”
Section: Effects Of Treatment On Panic Challengementioning
confidence: 56%
“…These findings are of interest considering that, contrary to SSRIs, tianeptine is believed to increase the 5-HT reuptake. A recent study by the Bristol group found that TD reversed the antipanic effect of chronic treatment with the SSRI paroxetine in PD patients, manifested as an increase in panicogenic response to a flumazenil challenge (Bell et al, 2002). This supports the assumption that SSRIs exert their therapeutic effects in PD by increasing the synaptic availability of 5-HT (Nutt et al, 1999).…”
Section: Effects Of Treatment On Panic Challengementioning
confidence: 72%
“…It has been used in studies of panic provocation [Bell et al, 2002;Nutt et al, 1990] and our previous 35% CO 2 studies . The PSI was adapted from Clark and Hemsley [1982] and was administered at baseline for peak effects of inhalation and at the end of each inhalation.…”
Section: Subjective Ratingsmentioning
confidence: 99%
“…For the pathophysiology of panic disorder, the serotonergic system has been considered as performing a role as inferred by challenge studies [41], serotonergic treatment studies [44,45], and brain imaging studies [46]. Since the serotonin transporter regulates serotonergic neurotransmission, 5-HTTLPR has been studied to demonstrate particular associations in research on panic disorder.…”
Section: Discussionmentioning
confidence: 99%